Tinjauan Hukum Ekonomi Syariah terhadap Perlindungan Konsumen dalam Praktik Jual Beli Snack Repacking - Deo Aprendi Yusuf; Moh. Yasir Fauzi; Pramudya Wisesha (Kartika: Jurnal Studi Keislaman, 2026)
Studies examining snack repacking practices in traditional markets from the perspective of Islamic Economic Law, particularly in relation to consumer protection, remain limited. This study aims to examine the practice of snack repacking transactions in Baradatu Market, Way Kanan Regency, and to assess their compliance with the principles of Islamic Economic Law. This research employed a qualitative field research approach. Primary data were collected through interviews with five snack repacking traders, three shop owners, and seven consumers, while secondary data were obtained from relevant literature, legal regulations, and supporting documents. Data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative techniques. The findings indicate that snack repacking provides economic benefits for small-scale traders and improves consumers' access to affordable products. However, most repackaged products lack essential information, including expiration dates, ingredient composition, and producer identity. From the perspective of Islamic Economic Law, snack repacking is fundamentally permissible because it fulfills the essential elements and conditions of a valid sale contract. Nevertheless, incomplete product information may give rise to gharar (uncertainty) and tadlis (deceptive practices), indicating that the practice has not fully complied with the principles of amanah (trustworthiness), shiddiq (truthfulness), and consumer protection